PEMAHAMAN MAHASISWA DAN KARYAWAN TERHADAP ADIPURA - Hadinoto, Hadinoto; Suhesti, Eni (Fakultas Kehutanan Universitas Lancang Kuning, 2016)
One of the government's efforts in maintaining the ecological balance in urban areas is to give an award in the form of